Engineering education in Russia in the context of socio-historical development (18 - early 20 centuries) - Olga V. Toporkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article considers the history of engineering education in our country in the pre-revolutionary period. What makes the study topical is the need for scientific understanding of the historical and pedagogical process of the development of Russian higher technical education, which will contribute to understanding its current state and determining the prospects for its development. As a result of the historical and pedagogical analysis, four stages of development of Russian higher technical education are defined: the stage of the emergence of professional technical education (the eighteenth century), the stage of the establishment of the system of technical education in Russia (the end of the 18th to the 50-s of the 19th century), the stage of increasing centralization in the management of the engineering education system (60-s - the mid-90-s of the 19 century), the stage of priority development of the Polytechnic Higher School (the second half of the 90-s of the 19 century - 1917). The article also presents the main characteristics of traditional models of engineering education in the Russian Empire, which include specialized branch institutes that train engineers just for one industry; technological institutes, traditionally teaching mechanical engineers and chemical engineers; multi-specialty polytechnic institutes; non-state higher technical school. Polytechnic institutes received priority development in pre-revolutionary Russia, realizing the idea of a rational combination of encyclopedic knowledge and narrow specialization in technical education.